2010
DOI: 10.2337/dc10-0939
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Glycemic Control on the Prognosis of Japanese Patients Undergoing Percutaneous Transluminal Angioplasty for Critical Limb Ischemia

Abstract: OBJECTIVETo reveal the influence of preoperative factors on the prognosis of patients undergoing percutaneous transluminal angioplasty (PTA) for critical limb ischemia (CLI).RESEACH DESIGN AND METHODSWe recruited 278 Japanese patients who underwent PTA for CLI between 2003 and 2009. The outcome measures were mortality and major amputation. Cox proportional hazards regression analyses were performed.RESULTSThe prevalence of diabetes was 71%, and A1C was 7.0 ± 1.4%. The follow-up period was 90 ± 72 weeks, and 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 21 publications
4
51
1
2
Order By: Relevance
“…Previous findings showed that the presence of diabetes and the HbA 1C level have no relationship with death in patients with CLI who underwent EVT, but are prognostic factors for major amputation, 21 and the results of this study supported these findings. In diabetic patients, cilostazol improved AFS (HR, 0.68; 95% CI, 0.50-0.90; unadjusted P ϭ .008) and the limb salvage rate (HR, 0.49; 95% CI, 0.30-0.78; unadjusted P ϭ .003), but was ineffective for all-cause mortality (HR, 0.84; 95% CI, 0.60-1.16; P ϭ .28).…”
Section: Discussionsupporting
confidence: 91%
“…Previous findings showed that the presence of diabetes and the HbA 1C level have no relationship with death in patients with CLI who underwent EVT, but are prognostic factors for major amputation, 21 and the results of this study supported these findings. In diabetic patients, cilostazol improved AFS (HR, 0.68; 95% CI, 0.50-0.90; unadjusted P ϭ .008) and the limb salvage rate (HR, 0.49; 95% CI, 0.30-0.78; unadjusted P ϭ .003), but was ineffective for all-cause mortality (HR, 0.84; 95% CI, 0.60-1.16; P ϭ .28).…”
Section: Discussionsupporting
confidence: 91%
“…A few recent studies reported that poor glycemic control 10,11) and insulin use 19) were associated with limb prognosis in CLI patients, but each study adopted only one DM-related variable and lacked adjustment for other diabetic conditions, including diabetic duration. DM patients under insulin therapy would tend to have a longer diabetic duration and a poorer glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…These unfavorable phenomena could cause a poor prognosis of CLI and a few recent studies have shown that poor glycemic control evaluated with hemoglobin A1c (HbA1c) was significantly associated with limb loss 10,11) ; however, no reports have ever discussed the diabetic duration. Long exposure to DM is associated with the progression of atherosclerosis 12) and it is well known that longer diabetic duration increases the risk of coronary heart disease and stroke in diabetic patients, independently of their glycemic control 13,14) .…”
Section: Introductionmentioning
confidence: 99%
“…Lower extremity arterial disease is a major cause of ischemic limb, delayed wound healing, and leg amputation in diabetic patients [11]. Diabetic patients have higher arterial rigidity and greater vascular resistance to blood flow, resulting in reduced blood supply in the lower-extremity arteries despite normal ankle-brachial index (ABI) [12].…”
Section: Subjectsmentioning
confidence: 99%